ECOBRICK SEBAGAI SOLUSI DALAM MENGURANGI TIMBULAN SAMPAH PLASTIK DI KELURAHAN KEPOLOREJO KECAMATAN MAGETAN KABUPATEN MAGETAN - Aulia .; Hery Koesmantoro; Susi Nurweni; Karno . (Jurnal Hygiene Sanitasi, 2022)
Waste management in Magetan Regency still uses a conventional system. Meanwhile, the amount of generated waste transported to the landfill will continue to increase along with the population growth and cause the landfill land to decrease. The purpose of this study was to determine the potential ecobricks as a solution in reducing the generation of plastic waste in Kepolorejo Urban Village, Magetan Sub district, Magetan Regency.  Sampling was carried out in accordance with SNI 19-3694-1994 at each hamlet in Kepolorejo Urban Village. Based on the results of sampling conducted on 33 families or 98 people spread across 12 hamlet in Kepolorejo Urban Village, the total waste generation generated in Kepolorejo Urban Village is 253.4 kg. the total plastic waste generation in Kepolorejo Urban Village is 18.8 kg consisting of plastic waste that can be used as ecobrick raw material, which is 11.9 kg/day and plastic waste that cannot be used as ecobrick raw material, which 6.9 kg. the value of the potential for ecobrick in reducing the generation waste in Kepolorejo is 4.6%. the number of ecobrick that can be produced in 1 year is 99.631.